Emka Amasiko Magwala Ndini: An Artistic Investigation of AmaXhosa through exploring Identity and Spirituality - Botozo, Lwandiso (Stellenbosch : Stellenbosch University, 2023)
Thesis MA (VA)--Stellenbosch University, 2023.